Trees and Multistorey Agriculture in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The book sets out to explain trees as a fundamental form of life, and to recognise the benefits which can be derived from their presence in terms of production, fertilisation, animal feed, energy, as well as the ecological services they render to...